IMPACT OF EMOTIONAL DYSREGULATION IN BORDERLINE PERSONALITY DISORDER: FEASIBILITY STUDY OF EIDETIC IMAGERY APPROACH - Zaheer, Maliha; Masroor, Uzma; Salik, Semra (Pakistan Journal of Clinical Psychology, 2025)
Objectives: The study aimed to investigate the therapeutic potential of Eidetic Psychotherapy for individuals with Borderline Personality Disorder (BPD), focusing on emotional instability. Design of the Study: Quasi Experimental Design Place and Duration of Study: Jan to June, 2022 Air University, Islamabad Sample and method: For this study ten female participants were recruited, they were antecedently diagnosed with BPD. The assessment of BPD was carried out using two assessment tools: The Borderline Symptom List (BSL-23) and the Strengths and Difficulties Questionnaire (SDQ 18+). Results and Conclusion: The results of our study revealed the effectiveness of the intervention, as evidenced by a decrease in scores after the application of the intervention, indicating a reduction in symptoms. Scores were relatively high but they were significantly decreased. The Wilcoxon signed-rank test further supported the potential efficacy of Eidetic psychotherapy, showing a significant reduction in scores after the intervention. This study highlights the potential of Eidetic Psychotherapy as a valuable tool for treating individuals with BPD.